Development of Chemical Equilibrium E-Module Guided by 5E Instructional Model with Interactive Virtual Laboratory - Lubis, Amalia Putri; Ellizar, Ellizar; Zainul, Rahadian; Nizar, Umar Kalmar (FKIP Universitas Lampung, 2022)
E-module is a form of electronic teaching material that can be used independently, with each learning activity connected by a link. 5E Instructional Model is a learning model that was developed based on constructivism learning, where students construct their own knowledge and are actively involved in every stage of the learning process. This study aims to develop a chemical equilibrium e-module based on an integrated 5E instructional virtual laboratory, as well as to determine the level of validity and practicality. The development of the e-module is carried out through the Plomp model stage which consists of 3 stages, namely preliminary research, prototyping phase, and assessment phase. The assessment instruments used are observation sheets and questionnaires. The results showed that the e-module developed was valid and practical so that it could be used in the learning process.Keywords: e-modul, 5E instructional model, chemical equilibriumDOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp256-265